The Effectiveness Of Using Digital Comic-Based Media In Increasing Social Studies Learning Outcomes - Mamur Ramdani; Eldi Mulyana; Slamet Nopharipaldi Rohman; Triani Widyanti; Tetep .; Asep Supriyatna; Yopi Nugraha (Institut Pendidikan Indonesia, 2021)
This research is motivated by the low social studies learning outcomes that occur in students in class VIII SMP Islam As-Syarief. The low social studies learning outcomes are caused by several factors, one of which is the use of social studies learning methods and media that are less attractive and do not invite students to be actively involved in the learning process. Researchers tried to use comic-based worksheets for learning media aimed at improving social studies learning outcomes. The method used is a quasi-experimental research design with a nonequivalent [pre-test and post-test] control group design. The population in this study were eighth grade students of SMP Islam As-Syarief. The samples taken were class VIII-C and VIII-E. Data was obtained by means of tests (pre-test and post-test), and observation sheets. Data analysis was performed using the Lilliefors normality test (Kolmogorov-Smirnov and Shapiro-Wilk), the Mann Whitney test, and the normalized Gain test. The results showed that learning using comic- based worksheets was effective in improving social studies learning outcomes for students, it was based on the average value of social studies learning outcomes after treatment was higher than before. The conclusion of this study is that comic-based worksheets are effective in improving social studies learning outcomes for class VIII students of SMP Islam As-Syarief.